Enhanced SFWBP Framework for Demand Evaluation of Public Sports Services for the Elderly in Rural Areas - Xiaoping Yang; Xiang Gu (International Journal of Agricultural and Environmental Information Systems, 2026)
Rural residents account for a substantial proportion of China's total population, and improving their physical fitness is pivotal to elevating the overall national fitness level. A thorough insight into public sports services for the rural elderly is essential to analyze the current service system, clarify its underlying logic, and formulate targeted optimization strategies. The demand evaluation for these services falls into the multi-attribute group decision-making (MAGDM) category. Spherical fuzzy sets (SFSs) provide a more effective and comprehensive tool to tackle the uncertainty and vagueness in subjective demand assessment. This study develops spherical fuzzy bidirectional projection (SFBP) and weighted SFWBP techniques by introducing the bidirectional projection method into the SFS environment. The authors build a complete MAGDM framework with detailed computational steps, validate the SFWBP method via a numerical case of rural elderly sports service demand evaluation, and conduct comparative analyses to verify its superiority in the SFS context.